2015
DOI: 10.1590/1678-4162-6816
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de genótipos de frangos tipo caipira

Abstract: RESUMOObjetivou-se com este trabalho comparar o padrão de crescimento, mediante ajustes das respectivas curvas de crescimento por modelos não lineares, bem como estudar o desenvolvimento de cortes de carcaça em relação ao peso da carcaça em diferentes genótipos de frangos tipo caipira. Foram utilizados 840 pintos de um dia, machos, distribuídos em delineamento inteiramente ao acaso, dos seguintes genótipos da linhagem Redbro: Caboclo, Carijó, Colorpak, Gigante Negro, Pesadão Vermelho, Pescoço Pelado e Tricolor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
5
1
1
Order By: Relevance
“…In contrast to the present study, several are the authors in the literature (Mota et al, 2015;Veloso et al, 2015;Finco et al, 2016), that It wasn't recommended the use of Brody for the description of bird growth, due to low quality adjustment to the data. However, as the present work deals of data of gut length and not of weight of the variable in question, and by the increase of gut length be rapidly in the first days after the birth of the quail, It are some peculiarities that may explain this better adjustment of Brody, already that this model is not indicated to predict the live weight in the early stages of animal growth (Brody, 1945).…”
Section: Comparison Of the Quality Adjusting Of Nonlinear Models For contrasting
confidence: 61%
See 1 more Smart Citation
“…In contrast to the present study, several are the authors in the literature (Mota et al, 2015;Veloso et al, 2015;Finco et al, 2016), that It wasn't recommended the use of Brody for the description of bird growth, due to low quality adjustment to the data. However, as the present work deals of data of gut length and not of weight of the variable in question, and by the increase of gut length be rapidly in the first days after the birth of the quail, It are some peculiarities that may explain this better adjustment of Brody, already that this model is not indicated to predict the live weight in the early stages of animal growth (Brody, 1945).…”
Section: Comparison Of the Quality Adjusting Of Nonlinear Models For contrasting
confidence: 61%
“…Some authors as Veloso et al (2015), already indicated the Von Bertalanffy model for the description of body growth of colonial-type broilers, using an experimental period of one to 84 days of age.…”
Section: Comparison Of the Quality Adjusting Of Nonlinear Models For mentioning
confidence: 99%
“…De maneira geral, não existe um consenso sobre a superioridade de uma linhagem em específico nos estudos já realizados comparando diferentes linhagens de aves de crescimento lento no Brasil (SANTOS et al 2005, TAKAHASHI et al 2006, MADEIRA et al 2010, VELOSO et al 2015, VELOSO et al 2014. Com o avanço da genética, todos os anos surgem linhagens de crescimento lento melhoradas, dentre elas, destacam-se as de origem francesa, tais como a Pescoço Pelado ou Redbro Cou Nu (Label Rouge), Redbro Plumé (Pesadão), Gris Barré Plumé (Carijó) e Master Gris Plumé (Master Gris) (MOREIRA 2012).…”
Section: Resultsunclassified
“…The SPSS 17.0 software package (SPSS Inc., Chicago, IL, USA) was used to analyze the data. Three nonlinear growth models, including logistic, Gompertz, and von Bertalanffy, were used to fit the growth curves of the geese [5][6][7]. The equations of these three nonlinear models are shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%